Pronunciation difficulty, temporal regularity, and the speech-to-song illusion - Margulis, Elizabeth H.; Simchy-Gross, Rhimmon; Black, Justin L. (Frontiers in Psychology, 2015)
The speech-to-song illusion (Deutsch, Henthorn & Lapidis, 2011) tracks the perceptual transformation from speech to song across repetitions of a brief spoken utterance. Because it involves no change in the stimulus itself, but a dramatic change in its perceived affiliation to speech or to music, it presents a unique opportunity to comparatively investigate the processing of language and music. In this study, native English speaking participants were presented with brief spoken utterances that were subsequently repeated ten times. The utterances were drawn either from languages that are relatively difficult for a native English speaker to pronounce, or languages that are relatively easy for a native English speaker to pronounce. Moreover, the repetition could occur at regular temporal intervals, allowing the emergence of a sort of meter, or at irregular temporal intervals, making the emergence of meter impossible. Participants rated the utterances before and after the repetitions on a 5-point Likert-like scale ranging from “sounds exactly like speech” to “sounds exactly like singing.” The difference in ratings before and after was taken as a measure of the strength of the speech-to-song illusion in each case. The speech-to-song illusion occurred regardless of whether the repetitions were spaced at regular temporal intervals or not; however, it occurred more readily if the utterance was spoken in a language difficult for a native English speaker to pronounce.